(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Solar energy devices, after a time has passed since their use, become older, their exposure to failure increases, their maintenance costs increase, and their production decreases. Thus, one solution is to replace them with a new device; this is referred to as preventive device replacement. Materials and Methods: When a solar panel fails, its life is over, and it is replaced. Alternatively, when it reaches the age ????1, a preventative solar panel replacement is implemented. Results: This work aims to identify the optimal time for the preventive replacement of solar energy devices, as the continued operation of an old device increases costs and necessitates a replacement that reduces maintenance costs and maintains the device’s production continuity. The current research identifies the optimal time for preventive replacement of solar energy devices synthesized from n similar tubes, as their failure and replacement costs increase as they age. As for devices consisting of large solar panel, the cost of panel failure is expensive and replacing them is expensive. Conclusions: The researcher studied the best time to replace panel with new panel, and that is before the panels fail. At the end of the paper, we identified some industrial and economic decisions that affect the life of replacing these two types of devices.